Criminal Execution Of Payment Of Compensation What The Public Prosecutor Did In The Case Of Corruption - Christine Natalia Pangaribuan; Suci Ramadani; Muhammad Arif Sahlepi (International Journal of Society and Law, 2025)
This study analyzes the effectiveness and challenges of the Public Prosecutor (JPU) as the sole executor in carrying out the penalty of paying substitute money (UP) in corruption cases. Replacement money, which is regulated in Article 18 of the Corruption Law, is an additional criminal sanction that is essential to recover state financial losses (asset recovery). This normative-empirical legal research identifies that normatively the prosecutor has the strong authority to confiscate and auction the assets of the convict if the UP is not paid within one month. However, in practice, the prosecutor faces significant obstacles, mainly due to: 1) The act of transferring the convict's assets triggers a lawsuit against a third party (derden verzet), which delays the execution process; and 2) Technical limitations in asset tracing to track assets disguised through money laundering schemes. It was concluded that it is necessary to strengthen synergy between institutions and the optimal use of TPPU legal instruments to ensure the success of asset recovery and achieve restorative criminal law goals.